Social transformation and studentification: a portrait of gentrification in jatinangor education area - Fitriani Fazrin; Fitria Zahrah; Emil Rahmansyah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The presence of a large university and an increase in the number of students have driven significant changes, including shifts in land use, increases in property prices, and changes in patterns of social interaction between students and local residents. This research aims to examine the social, economic, and cultural impacts of studentification and gentrification in the Jatinangor education area. Using a qualitative approach through in-depth interviews, field observations, and secondary data analysis, this research explores how these transformations affect Jatinangor's community character and cultural identity. The results show that studentification in Jatinangor not only brings new economic opportunities, but also triggers social challenges for the indigenous population, especially related to economic pressures and cultural changes. This study makes an important contribution to the understanding of the dynamics of gentrification in educational areas and provides policy recommendations to support the balance between educational development and socio-cultural sustainability for local communities.